Aspectos clínicos e funcionais da síndrome dolorosa miofascial em indivíduos com dor no ombro - Nascimento, José Diego Sales do (2021)
The overall purpose of this doctorate thesis were to present information on the clinical aspects that involve the presence of myofascial trigger points (MTP) in shoulder and neck muscles, to verify the relationship between MTP and the clinical variables of pain, psychological aspects, mobility and strength and the effects of a physical therapy approach on these aspects in individuals with non-traumatic shoulder pain. To this end, three studies were carried out: Study 1 - Myofascial pain and trigger points in the shoulder and neck region: from concept to physical therapy management; Study 2 - Relationship and predictive capacity between active myofascial trigger points and physical, clinical and psychological characteristics in individuals with shoulder pain; Study 3 - Immediate effects of ischemic compression on myofacial trigger points on pain, mobility and strength in individuals with subacromial impact syndrome: a single arm study. The study 1 is a literature review on MTPs in the shoulder and neck region that addresses definitions, assessment reliability, sensitization phenomena, differential diagnosis, the relationship of MTP with clinical variables and therapeutic management. Study 2 is a cross-sectional and observational study. A total of 58 individuals (36 men and 22 women, aged between 31 ± 10.91 years and BMI of 25.01 ± 3.42 kg/m²) participated in the study. All individuals were assessed for physical and demographic characteristics, depression symptoms, pain and shoulder function, presence of MTPs, ROM and pain during ROM and force. Pointbiserial (rpb) and Spearman (rs) correlation tests and multiple linear regression were used to assess the relationship between the presence and quantity of MTPs and the study variables, adopting a significance value of p<0.05. The presence and quantity of MTPs generally correlated between weak to moderate with depression symptoms, pain during sagittal flexion ROM and internal and external rotation, pain during sagittal lifting force, self-reported shoulder function and external rotation force. The presence of MTPs in the infraspinatus has been shown to influence depression symptoms; MTPs in the upper and lower trapezius influenced pain during the internal rotation ROM; MTPs in the upper trapezius influenced pain during internal rotation force; and MTPs in the supraspinatus influenced pain during external rotation ROM. There is a weak to moderate correlation between the presence and quantity of active MTPs and depression symptoms, pain during shoulder ROM and force, ROM, force, and self-reported function. Study 3 is a single-arm study. A total of 15 individuals (6 women and 9 men, 34.4 ± 10.43 years and 24.20 ± 2.18 kg/m2) with clinical symptoms of unilateral SIS. All individuals were assessed for the amount of MTPs in the shoulder muscles; pressure pain threshold (PPT) in shoulder muscles; range of motion of the shoulder; isometric strength of shoulder muscles; and pain in performing ROM and isometric strength contraction. The evaluations took place 48 hours before the ICT, immediately before, and after the ICT. There was a reduction in the total amount of MTPs and an increase in the PPT in the middle deltoid muscle in the comparisons between pre and post treatment, while there was no difference in ROMs and strength measures; however, the pain was less during the sagittal elevation ROM and internal rotation, and during the performance of strength in arm elevation and external rotation. There was generally no difference in the variables assessed between baseline and pre-treatment. The ICT immediately reduced the amount of MTPs and pain during mobility and strength, but did not change the PPT, ROM or strength variables. The present study will support clinical practice in the management of shoulder and neck myofascial pain in the presence of MTPs.